Component database systems - Dittrich, Klaus R.; Geppert, Andreas (San Francisco : Morgan Kaufmann Publishers, 2001)
Component Database Systems is a collection of invited chapters by the researchers making the most influential contributions in the database industry's trend toward componentization This book represents the sometimes-divergent, sometimes-convergent approaches taken by leading database vendors as they seek to establish commercially viable componentization strategies. Together, these contributions form the first book devoted entirely to the technical and architectural design of component-based database systems. In addition to detailing the current state of their research, the authors also take up many of the issues affecting the likely future directions of component databases. If you have a stake in the evolution of any of today's leading database systems, this book will make fascinating reading. It will also help prepare you for the technology that is likely to become widely available over the next several years. * Is comprised of contributions from the field's most highly respected researchers, including key figures at IBM, Oracle, Informix, Microsoft, and POET. * Represents the entire spectrum of approaches taken by leading software companies working on DBMS componentization strategies. * Covers component-focused architectures, methods for hooking components into an overall system, and support for component development. * Examines the component technologies that are most valuable to Web-based and multimedia databases. * Presents a thorough classification and overview of component database systems.
Chapter 1 -- Component Database Systems: Introduction, Foundations and Overview -- Chapter 2 -- Distributed Component Database Management Systems -- Chapter 3 -- All Your Data: The Oracle Extensibility Architecture -- Chapter 4 -- Extensible Indexing Support in DB2 Universal Database -- Chapter 5 -- Enabling Component Databases with OLE DB -- Chapter 6 -- An Architecture for Transparent Access to Diverse Data Sources -- Chapter 7 Building Component Database Systems Using CORBA -- Chapter 8 -- The Architecture of a Database System for Mobile and Embedded Devices -- Chapter 9 -- Conclusions and Perspectives.
Includes bibliographical references (p. [263]-279) and index.
Keywords: Database management; Distributed databases; Electronic books